Assembly of different isoforms of actin and tropomyosin into the skeletal tropomyosin-enriched microfilaments during differentiation of muscle cells in vitro (The Rockefeller University Press, 1986)
We have used a monoclonal antibody (CL2) directed against striated muscle isoforms of tropomyosin to selectively isolate a class of microfilaments (skeletal tropomyosin-enriched microfilaments) from differentiating muscle cells. This class of microfilaments differed from the one (tropomyosin-enriched microfilaments) isolated from the same cells by a monoclonal antibody (LCK16) recognizing all isoforms of muscle and nonmuscle tropomyosin. In myoblasts, the skeletal tropomyosin-enriched microfilaments had a higher content of alpha-actin and phosphorylated isoforms of tropomyosin as compared with the tropomyosin-enriched microfilaments. Moreover, besides muscle isoforms of actin and tropomyosin, significant amounts of nonmuscle isoforms of actin and tropomyosin were found in the skeletal tropomyosin-enriched microfilaments of myoblasts and myotubes. These results suggest that different isoforms of actin and tropomyosin can assemble into the same set of microfilaments, presumably pre-existing microfilaments, to form the skeletal tropomyosin-enriched microfilaments, which will eventually become the thin filaments of myofibrils. Therefore, the skeletal tropomyosin-enriched microfilaments detected here may represent an intermediate class of microfilaments formed during thin filament maturation. Electron microscopic studies of the isolated microfilaments from myoblasts and myotubes showed periodic localization of tropomyosin molecules along the microfilaments. The tropomyosin periodicity in the microfilaments of myoblasts and myotubes was 35 and 37 nm, respectively, whereas the nonmuscle tropomyosin along chicken embryo fibroblast microfilaments had a 34-nm repeat.